Secularist understandings of Pentecostal healing practices in Amsterdam: Developing an intersectional and post-secularist sociology of religion - Knibbe, Kim Esther (Social compass, 2018)
The past decades have seen an intensification of debate around migrants, gender and sexuality. For the Netherlands, several authors have pointed out how this has given rise to a form of sexual nationalism whereby the idea of being a modern, progressive country is strongly linked to a program of liberal sexual values and offset against a presumably backward' migrant who is still' religious and traditional. In this article, the author analyses how these dynamics played out in the controversy around HIV-healings or homo healings supposedly taking place in Pentecostal churches in Amsterdam. Media attention highlighted the theme of homosexuality while forgetting the interests of women. This article shows that the sexual nationalism scheme was also operative here, and proposes further developing existing approaches as intersectional post-secularist' sociological perspectives aimed at unearthing the ways narratives of modernity, secularization and sexual nationalism structure attitudes towards migrant and religious actors both in social scientific research agendas and among societal actors.